Multivitamin supplementation and its impact in metabolic dysfunction-associated steatotic liver disease - Tom Ryu; Seung Yun Chae; Jaejun Lee; Ji Won Han; Hyun Yang; Beom Sun Chung; Keungmo Yang (Scientific Reports)
Abstract Metabolic dysfunction-associated steatotic liver disease (MASLD) is an emerging global health concern with limited therapeutic options. Multivitamins, widely consumed dietary supplements, have been proposed to modulate oxidative stress and inflammation, potentially impacting MASLD progression. However, their efficacy in reducing mortality and other complications in MASLD remains unclear. Using data from the UK Biobank with 7 years of median follow-up period, this study assessed the association between multivitamin use and health outcomes, including all-cause mortality, liver-related mortality, cardio-cerebrovascular disease (CVD), and chronic kidney disease (CKD), in individuals with MASLD and those without steatotic liver disease. Inverse probability of treatment weighting (IPTW) was employed to adjust for confounders. Multivitamin users showed a significantly lower all-cause mortality risk in the MASLD cohort both before (HR: 0.88, 95% CI 0.81–0.95, P = 0.034) and after (HR: 0.94, 95% CI 0.88–1.00, P = 0.037) IPTW adjustment. Multivitamin use was also associated with the lower risk of CVD (HR: 0.72, 95% CI 0.68–0.76, P < 0.001) and CKD (HR: 0.73, 95% CI 0.67–0.81, P < 0.001) in the MASLD cohort. No significant reduction was found for liver-related mortality or liver cirrhosis incidence. These findings suggest that multivitamins might provide broader protective effects in populations with metabolic dysfunction. Further research is needed to clarify their role in liver-specific outcomes.